PENGARUH KELOMPOK RUJUKAN DAN KEPRIBADIAN OTORITARIAN TERHADAP PERILAKU MEMILIH PADA PEMILIH PEMULA - Zulaeni Esita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
The numbers of golput increasing in Indonesia each election after reform, it became a threat to the democratic process of this nation. Recorded in 2004, the number of golput increased to 23% from the previous election period and it’s number increased again to 39% in 2009. The voters more apathetic and do not care again about the fate of their country, so it was supposed to be a concern, especially for young voters as the next generation of the democratic process. This study focused on the factors that influence voting behavior, especially the influence of the authoritarian personality and the influence of a reference group for young voters. Voting behavior equated with purchasing behavior, so that voters are seen as political consumers. This study was designed to quantitatively, the data were analyzed using path analysis because the independent variables affect the dependent variable directly and indirectly. The results showed that the authoritarian personality directly by 0,365 ( β = 0.365 , p <0.05 ) influence voting behavior for young voters. Reference group has no direct influence on the voting behavior for young voters, but it indirectly through the authoritarian personality affect voting behavior for young voters. Reference group that directly influence young voter’s authoritarian personality is the parent ( β = 0.128 , p <0.05 ) and peers ( β = - .198 , p <0.05 ).